Evaluation of California's Armed and Prohibited Persons System: study protocol for a cluster-randomised trial. Issue 5 (11th October 2016) - Wintemute, Garen J; Beckett, Laurel; Kass, Philip H; Tancredi, Daniel; Studdert, David; Pierce, Glenn; Braga, Anthony A; Wright, Mona A; Cerdá, Magdalena
Abstract : Background and objective: Too little is known about the effectiveness of efforts to prevent firearm violence. Our objective is to evaluate California's Armed and Prohibited Persons System (APPS), a law enforcement intervention that seeks to recover firearms from individuals who purchased them legally but subsequently became prohibited from having access to firearms. Prohibitions usually arise from events suggesting an increased risk for future violence. Design and study population: This group-randomised trial involves approximately 20 000 APPS-eligible individuals in 1041 communities. Randomisation was performed at the community level, to early or later intervention (Group 1 and Group 2, respectively) with stratification by region, population and violent crime rate. Methods: APPS is being implemented by the California Department of Justice. The principal outcome measure is the incidence of arrest for a firearm-related or violent crime. Primary analysis will be on an intention-to-treat basis, comparing individuals in Group 1 and Group 2 communities. Analyses will focus on time to event, using proportional hazards regression with adjustment for the clustered nature of the data and incorporating individual- and community-level characteristics. Secondary analyses will examine the effect of the intervention on an as treated basis, effects on subgroups, and effects on community-wide measures such as crime rates. Discussion: APPS may have a significant impact on risk for future violence among members of its target population. The findings of this study will likely be generalisable and have clear implications for violence prevention policy and practice. Trial registration number: NCT02318732.